2020
DOI: 10.1002/eji.202048558
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans bind human IL‐27 and regulate its activity

Abstract: IL-27 is a cytokine of the IL-12 family, composed of EBI3 and IL-27p28. IL-27 regulates immune responses and also other physiological processes including hematopoiesis, angiogenesis, and bone formation. Its receptor, composed of IL-27Rα and gp130, activates the STAT pathway. Here, we show that different glycosaminoglycans (GAGs) modulate human IL-27 activity in vitro. We find that soluble heparin and heparan sulfate efficiently inhibit human IL-27 activity as shown by decreased STAT signaling and downstream bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For example, sulfation of cell surface proteoglycans is required for IL-10-mediated effects on monocytes and macrophages whereas IL-10 interacting with soluble HS can inhibit these same effects, and similarly opposite consequences of soluble versus cell-anchored HS are observed for IL-27-mediated effects on T-cell activation ( Salek-Ardakani et al. 2000 ; Cavé et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sulfation of cell surface proteoglycans is required for IL-10-mediated effects on monocytes and macrophages whereas IL-10 interacting with soluble HS can inhibit these same effects, and similarly opposite consequences of soluble versus cell-anchored HS are observed for IL-27-mediated effects on T-cell activation ( Salek-Ardakani et al. 2000 ; Cavé et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…to human and mouse IL-27, thereby regulating the activation of STAT1 and STAT3 112 . Furthermore, STAT3 mediates endothelial dysfunction and plays a key role in sepsis-induced multiple organ failure by inducing disseminated intravascular coagulation (DIC) 71,113 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“… 109 Cavé et al proved that GAGs bind to human and mouse IL-27, thereby regulating the activation of STAT1 and STAT3. 110 Furthermore, STAT3 mediates endothelial dysfunction and plays a key role in sepsis-induced multiple organ failure by inducing disseminated intravascular coagulation. 71 111 Beckman et al, using vascular endothelial cells, found that JAK-STAT inhibition limited the secretion of pro-adhesive and procoagulant factors.…”
Section: Gags and Coagulopathymentioning
confidence: 99%